Beyond the tumor: endocrine and metabolic dysregulation in intracranial germ cell tumors – a retrospective cohort study - Serra, Mayco José Reinaldi; Spinola-Castro, Angela Maria; Silva, Nasjla Saba da; Cappellano, Andrea; Okuda, Paola Matiko Martins; Siviero-Miachon, Adriana Aparecida (Arquivos de Neuro-Psiquiatria, 2025)
Intracranial germ cell tumors (iGCTs) often lead to endocrine-metabolic complications; however, their long-term effects are not well understood and characterized.To evaluate endocrine-metabolic dysfunction before and after iGCTs treatment.The present retrospective study included 99 patients with iGCTs treated at a tertiary hospital. Endocrine and metabolic parameters were assessed before and after treatment.A male sex predominance was observed (81.8%). The leading site was pineal (44.4%), and 67.7% of the tumors were classified as germinoma. Radiotherapy was performed in 82.8% of the cases (58.5% cranial and 41.5% craniospinal). At diagnosis, the incidences of gonadotropin-independent precocious puberty and diabetes insipidus were 15.2% and 48.2%, respectively. Significant endocrine-metabolic changes in patients with iGCTs were observed after treatment, as 72.3% of patients required hormone replacement, 60% had growth hormone deficiency, and dyslipidemia was observed in 49.2% of patients. Overweight increased from 24.2 to 35.4% after treatment, while obesity increased from 10.1 to 15.4%. There was an increase in growth hormone deficiency, hypothyroidism, and hypogonadism, while prolactin levels significantly decreased after treatment. An older age at diagnosis was associated with a lower risk of hypocortisolism (p = 0.005). Regarding sex, females had lower height Z-scores and a higher frequency of growth hormone deficiency compared with males. Tumor-related mortality was reported in 22.2% of patients, occurring on average 2.2 years postdiagnosis.The high prevalence of endocrine-metabolic complications following radiotherapy highlights the necessity of ongoing monitoring. The treatment demonstrated significant efficacy, as reflected by the notable survival rates. Early intervention is crucial for improving the long-term quality of life.
Keywords: Germinoma; Central Nervous System Diseases; Hypopituitarism; Obesity; Diabetes Insipidus; Radiotherapy